KLIREN DAN VOLUME DISTRIBUSI - Aluwi Sani (JURNAL ILMU KEFARMASIAN INDONESIA, 2003)
The concept and terminology of pharmacokinetics might be forgotten already by pharmacists. Therefore, the writer plans to present a series of article explaining the meaning and significant important pharmacokinetics terms. This article will deal with Clearance (CL) and Volume of Distribution (Vd), which are the two most important primary pharmacokinetic parameters. Other parameters such as t' and AUC are derived from these two parameters. Definition, function and measurement will be discussed in this article.